Fertility and Symptom Relief following Robot-Assisted Laparoscopic Myomectomy - Michael C. Pitter; Serene S. Srouji; Antonio R. Gargiulo; Leslie Kardos; Usha Seshadri-Kreaden; Helen B. Hubert; Glenn A. Weitzman (Hindawi Limited, 2015)
Objective. To examine success of robot-assisted laparoscopic myomectomy (RALM) measured by sustained symptom relief and fertility. Methods. This is a retrospective survey of 426 women who underwent RALM for fibroids, symptom relief, or infertility at three practice sites across the US. We examined rates of symptom recurrence and pregnancy and factors associated with these outcomes. Results. Overall, 70% of women reported being symptom-free, with 62.9% free of symptoms after three years. At >3 years, 66.7% of women who underwent surgery to treat infertility and 80% who were also symptom-free reported achieving pregnancy. Factors independently associated with symptom recurrence included greater time after surgery, preoperative dyspareunia, multiple fibroid surgeries, smoking after surgery, and preexisting diabetes. Factors positively correlated with achieving pregnancy included desiring pregnancy, prior pregnancy, greater time since surgery, and Caucasian race. Factors negatively correlated with pregnancy were advanced age and symptom recurrence. Conclusions. This paper, the first to examine symptom recurrence after RALM, demonstrates both short- and long-term effectiveness in providing symptom relief. Furthermore, RALM may have the potential to improve the chance of conception, even in a population at high risk of subfertility, with greater benefits among those who remain symptom-free. These findings require prospective validation.